Determinants of Economic Sustainability in Higher Education Institutions - Juraj Chebeň; Drahoslav Lančarič; Michal Munk; Peter Obdržálek (Amfiteatru Economic)
Despite the attention being paid to the environmental and social dimension of sustainability of Higher Education Institution (HEI) in the literature, little empirical research has focused on economic sustainability considering the HEI as an entity depending on financial funds provided by students, research, strategic partners, effective and efficient financial management. The conducted empirical survey deals with the link between the performance of HEI (number of students and the research productivity) and its economic sustainability measured as the average share of government subsidy. Furthermore, based on the 4678 students´ questionnaires, the paper explores the perception of the quality of study and the capabilities of graduates of public HEIs in Slovakia. The authors have used Multivariate Tests of Significance to evaluate the influence of above-mentioned variables on the economic sustainability of HEIs. Based on the results it can be concluded the HEIs´ economic sustainability is directly determined by the number of enrolled students and research productivity, while the effect of the quality of study and the capabilities of graduates was not confirmed. Many HEI funding systems are based on the number of enrolled students. The funding system in Slovakia is one of them. Therefore, the results (even if drawing from the specific context) are widely applicable.The study theoretically contributes to the sustainability of HEI by proposing a general and a specific conceptual model of sustainability in HEI. Some HEI funding systems based on the number of enrolled students are planning to base their funding system on capabilities of graduates and their employability (e.g. Slovakia). This fact even highlights the real-life importance of our study. Research results also tell that the quality of study and the capabilities of graduates are perceived differently at the altered types of HEI. Several HEIs were identified and therefore, HEIs need to adopt different strategies to satisfy diverse stakeholders’ expectations.